الإسهامات اللسانية في تعليمية اللغات (مجلة إحالات, 2025)
اتسع وعي الناس باللسانيات وذلك لما تقدمه من ثمرات للعلوم ولا سيما في مجال حقل تعليم اللغات وبذلك تطورت منهجية تعليم اللغات حتى أضحت فرعا من اللسانيات بعدما استثمرت نتائجها المحققة في مجال البحث اللساني لترقية طرائق تعليم اللغات من خلال إسهامات اللسانيات في هذا الحقل.Absacrat :The linguistic awareness of the linguists has increased due to the fruits ofscience, especially in the field of language education.Thus, the methodology of language education has evolved into a branch of linguistics after investing its results in linguistic research to upgrade the methods of teaching languages through the contributions of linguistics in this field.